2016
DOI: 10.5535/arm.2016.40.4.568
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Attitude and Heading Reference System and Microsoft Kinect for Continuous Measurement of Cervical Range of Motion Compared to the Optical Motion Capture System

Abstract: ObjectiveTo compare optical motion capture system (MoCap), attitude and heading reference system (AHRS) sensor, and Microsoft Kinect for the continuous measurement of cervical range of motion (ROM).MethodsFifteen healthy adult subjects were asked to sit in front of the Kinect camera with optical markers and AHRS sensors attached to the body in a room equipped with optical motion capture camera. Subjects were instructed to independently perform axial rotation followed by flexion/extension and lateral bending. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…This finding is in agreement with the study by Young et al [30], who investigated the validity of the Microsoft Kinect™ in the assessment of continuous cervical motion. They compared the values of cervical spine measurements of the Kinect system and the optical motion capture system (MoCap).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in agreement with the study by Young et al [30], who investigated the validity of the Microsoft Kinect™ in the assessment of continuous cervical motion. They compared the values of cervical spine measurements of the Kinect system and the optical motion capture system (MoCap).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it should be pointed out that the Kinect has higher measurement errors in rotation angle measurements [33] in comparison with other cervical motions. Young et al [30] have found as high as 14.25⁰ measurement errors in axial rotation by the Kinect and this may be responsible for its lower correlation compared to other cervical motions as observed in our and other studies..…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations